Petrography and depositional environment of Permo-Triassic carbonates of Pahalgam Formation, Kashmir Himalaya, India (Journal of Nepal Geological Society, 1998)
The Permo-Triassic carbonates of the Pahalgam Formation are exposed in the vicinity of the Pahalgam area. The Pahalgam Formation is characterised by fossils like productus, bryozoans, Spirifer Rajah, crinoids and molluscs. The rocks of this formation are represented by white grey muddy limestones followed by grey crinoidal limestones with brachiopods and lamellerbranchs. The rocks extend towards, Chandanwari, Sheshnag, Amamath Cave, Sonamarg and then to the Ladakh region of Jammu and Kashmir State. The outcrops of this formation, extending from the Pahalgam village up to Aru via Mammal village, can be traced along the Lidder River. The formation is equivalent to the well-known Zewan Formation of the Vthi district both in lithology and fossil assemblages. On the basis of lithology, the Pahalgam Formation has been divided into three units i.e. Pahalgam unit, Mammal unit, and Aru unit. Thin sections from each unit of the Pahalgam Formation were prepared for the present study and examined with respect to texture, framework grains, cementation and palaeo-petrographical criteria. The textural parameters used to indicate different energy levels in deposition of these carbonates were the attrition of the bivalve fossils (brachiopods and pelecypods) and the context of the sparite cement. The Pahalgam Formation is of platform type on which carbonate sedimentation took place during the Permo-Triassic times. It is a type of lime mud cycle with essentially low energy carbonate deposition, representing restricted open marine environment.